Research on the Correlation Between Spatial Layout Characteristics and Geographical Conditions for Ethnic Minority Rural Settlements - Xi Luo; Jian Zhang (Land)
It is significant to study the correlation between the spatial distribution and topographic features for ethnic minority rural settlements, which can provide the theoretical basis and practical methods for the preservation of ethnic culture and scientific planning of territorial space. Liuzhou in Guangxi is a region with diverse ethnic groups and this paper takes Liuzhou as the case study. This study employs fractal theory, GIS spatial analysis, and correlation analysis methods to investigate the relationship between settlement spatial patterns and their surrounding geographical conditions. The findings reveal a significant positive correlation between the geographic location of ethnic minority rural settlements (including site selection and terrain features) and their geographical conditions (topographic and elevation factors). Additionally, significant associations exist between settlement slope, settlement orientation, and their positioning within mountainous terrain. The study also reveals strong correlations between planar morphological characteristics (or settlement scale) and settlement terrain for the settlements of the same ethnic group within the same region. Specifically, Dong settlements exhibit remarkable consistency in settlement scale, while Miao settlements demonstrate high similarity in terms of elevation distribution. The methodology developed in this study is applicable to correlation research on settlement characteristics across diverse ethnic groups and geographical regions. It not only reveals universal patterns of how physical-geographic environments influence the planar and spatial features of settlements, but also validates the logical coherence of investigating layout characteristics from both planar and spatial perspectives. The findings of this study not only provide practical guidance for the development and planning of settlements, but also offer recommendations for the cultural inheritance and settlement protection of ethnic minorities.